An investigation on the softening and ripening process of tropical mango (Mangifera indica L.) with a particular focus on Rab GTPases - Lawson, Tamunonengiyeofori (2019)
Mango (Mangifera indica L.) is an economically important fruit crop grown in the tropics. This crop species is popularly consumed as fruit in Malaysia. Once ripening is initiated, the process proceeds at a fast rate making postharvest life short. Excessive softening during ripening is a major challenge in the postharvest storage of fruits as it renders the fruits unfit for long term storage leading to heavy postharvest losses. The improved storage of mango fruit would greatly enhance the economic potential of this crop. Hence, an in-depth understanding of the ripening-related events is essential to facilitate the development of strategies to improve fruit quality and reduce post-harvest losses. Fruit softening during ripening involves the trafficking of cell wall polymers and enzymes. The Rab (Ras related proteins in brain) GTPase family are key players in vesicle trafficking. Therefore it is important to understand the linkage between the Rab (Ras related proteins in brain) GTPases and the differential softening rate in fruit varieties for effective postharvest management, hence this research.